The dynamics of social assistance benefit receipt in Britain - Lorenzo Cappellari; Stephen P. Jenkins (Institute for the Study of Labor (IZA), 2009)
We analyze the dynamics of social assistance benefit (SA) receipt among working-age adults in Britain between 1991 and 2005. The decline in the annual SA receipt rate was driven by a decline in the SA entry rate, rather than by the SA exit rate (which actually declined too). We examine the determinants of these trends using a multivariate dynamic random effects probit model of SA entry and exit probabilities applied to British Household Panel Survey data. The model estimates and accompanying counterfactual simulations highlight the importance of two factors - the decline in the unemployment rate over the period, and other changes in the socioeconomic environment including two reforms to the income maintenance system in the 1990s. The results also reveal a substantial heterogeneity in SA annual transition rates.
urn:nbn:de:101:1-200910141359
Keywords: I38; C33; C35; 330; Benefits; income dynamics; social assistance; welfare; dynamic random effects probit; Sozialhilfe; Sozialhilfeempfänger; Soziale Mobilität; Großbritannien